BUDAYA PERCERAIAN DALAM ALKITAB: Memahami Konteks Perceraian Dalam Budaya Yahudi dan Romawi - Pardede, Harold (Al Hikmah, 2024)
Divorce cases are often found in the context of today's society. The issues of divorce and adultery are also discussed in the biblical text with context. The purpose of this paper is to see how the views of both the old and new covenants talk about divorce. Since the Old Testament, Scripture has affirmed the integrity of a marriage in which God and His plan are present. The Lord Jesus himself reminded the Bible teaching about the marriage institution. The law of marriage must be in harmony with God's purpose for establishing marriage. Did the Old Testament context and culture allow divorce? Do the New Testament and God allow Jesus regarding the issue of husband and wife divorce? In this essay will be described in the literature how the principle of divorce in the Bible. This study uses literature research that summarizes several books and sources from both the old and new covenants regarding divorce.